Pengujian Aplikasi Pengenalan Tulisan Tangan menggunakan Model Behaviour Use case - Gita Fadila Fitriana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
Good software development must go through a testing process every phase. Testing is used to find software problems developed. Testing is done based on software development needs. This test validates the initial and final conditions as needed. In this study, testing with the behavior model Unifed Modelling Language (UML), namely use case diagrams. Based on test results, 15 tests are needed according to the usage scenario. Obtained 1 exam that was rejected, this was done an increase in the functionality of the Scenario results, based on this test, we can learn the quality of the handwriting application.